To simplify the expression \( 3 \sqrt{45} \), we can start by factoring \( \sqrt{45} \):
\[ \sqrt{45} = \sqrt{9 \times 5} = \sqrt{9} \sqrt{5} = 3\sqrt{5} \]
Now we substitute this back into the expression:
\[ 3 \sqrt{45} = 3 \times 3\sqrt{5} = 9\sqrt{5} \]
Now we can rewrite the equation as follows:
\[ \text{(blank)} \sqrt{5} + 9 \sqrt{5} = 13 \sqrt{(blank)} \]
Letting \( x \) represent the blank in the first part:
\[ x \sqrt{5} + 9 \sqrt{5} = (x + 9) \sqrt{5} \]
Setting it equal to the right-hand side:
\[ (x + 9) \sqrt{5} = 13 \sqrt{(blank)} \]
Next, we match the terms under the radicals. For the expression to match, \( \sqrt{(blank)} \) must also equal \( \sqrt{5} \), which means the blank is simply \( 5 \):
So we have: \[ x + 9 = 13 \]
Now we can solve for \( x \):
\[ x = 13 - 9 = 4 \]
Thus, we can fill in the blanks:
\[ 4 \sqrt{5} + 3 \sqrt{45} = 13 \sqrt{5} \]
The complete expression is:
4√5 + 3 √45 = 13√5.